Conceptual design of the HCCB blanket system integration for CFETR. (10th March 2019) - Lei, Mingzhun; Song, Yuntao; Liu, Sumei; Lu, Kun; Xu, Shuling; Xu, Kun
Summary: In a fusion power plant, the integration of the blanket system in the design progress is of vital importance to address the fundamental function of sufficient tritium production, reliable nuclear heat extraction, and permanent components protection due to the complex assembling systems into the tokamak vessel. Some progress activities of the blanket system design and integration for China fusion engineering test reactor (CFETR) are developed. The integration work involves the design of the breeding blanket, back plate support, shielding blanket, and supporting structures. To guarantee normal operation of the reactor, the design and arrangement of cooling pipes are very critical. The layout of the complex cooling pipes inside the blanket system is designed and integrated. Interfaces between main connecting components are designed for blanket system integration. In this work, the U‐shaped HCCB blanket is utilized as the adaption breeding module into the integrated blanket system. The three‐dimensional (3D) neutronic analyses verified that the integrated design of the blanket system could well meet the requirements of tritium self‐sufficiency and neutron shielding. The nuclear heat generation of main components in the reactor is obtained with a nuclear energy multiplication factor of 1.35. The primary principle during the integration is to accommodate all the components allocated on the vacuum vessel. This work is the preliminary integration design and validation for CFETR blanket system, and further detailed design will be performed around these obtained references for better fusion feasibility and performance in the next‐step design stage. Abstract : The integration of the blanket system in the fusion reactor design progress is of vital importance to address the fundamental function of sufficient tritium production, reliable nuclear heat extraction, and permanent components protection due to the complex assembling systems into the tokamak vessel. Some progress activities of the blanket system design and integration for China fusion engineering test reactor (CFETR) are developed. Conceptual design of the blanket components and some requirements have been described. The strategy of the interfacing design of the HCCB blanket system is presented. This work is the preliminary integration design and validation for CFETR blanket system, and further detailed design will be performed around these obtained references for better fusion feasibility and performance in the next‐step design stage.